Pengaruh Ukuran Komite Audit, Kepemilikan Manajerial dan Kepemilikan Institusional Terhadap Return On Assets (ROA) - Celine Eriskha; Nanu Hasanuh (COSTING : Journal of Economic, Business and Accounting, 2021)
When observing the major financial problems that were revealed, the public questioned the performance of the big companies involved in this scandal, which contradicts the principles of Good Corporate Governance regarding accountability, equity, integrity, transparency and responsibility. This study aims to determine, test and explain the effect of the audit committee, managerial ownership, institutional ownership, on Return On Assets both partially and jointly in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2014 to 2019. The sample was determined by purposive sampling. Data collection techniques using literature study and observation. The method used is multiple linear regression analysis. Based on the results of multiple linear analysis, it is found that Managerial ownership has a partial effect on ROA then Audit Committee Size and Institutional ownership partially have no effect on ROA, and simultaneously Audit Committee Size, Managerial Ownership and Institutional Ownership together have an effect on Return On Assets ( ROA). Keywords: Audit Committee, Managerial Ownership, Institutional and ROA